Análisis a los Estados Financieros de la Cooperativa de Ahorro y Crédito Educadores de Loja, de la ciudad de Loja, periodo 2019-2020 - Ojeda Garrido, Jessica Elizabeth (2023)
The present Title Work denominated Analysis of the Financial Statements of the “Cooperativa de Ahorro y Crédito Educadores de Loja”, of Loja City, Period 2019-2020; It was developed to meet the prerequisite for opting for the degree of Accounting and Auditing Engineer, Public Accountant Auditor, from Universidad Nacional de Loja. In addition to complying with the proposed objectives: analyze the financial statements through the vertical analysis of each study period with the purpose of obtaining the degree of participation of each account, the horizontal analysis establishing the financial movements and the variations of the different items. as its increases and decreases from one period to another, evaluated in the Statement of Financial Position and Statement of Income, in this way to be able to know the position of the Cooperative; It was evidenced that its assets in 2019 have a value of $27,656,612.98 and in 2020 of $29,998,144.66 concentrated mainly in current assets with 93.53% and 93.89% respectively, where they are significantly represented by Credit Portfolio with 79.71% and 69.51% being an essential element in a cooperative since they constitute the amounts of the credits granted to the members who in turn oblige to comply with their payments with their respective interest generated; in Liabilities, Obligations with the Public with 94.75% and 93.58% derived from the collection of resources from the public through deposits; in Patrimony, the Social Capital with 46.59% and 42.89% constituted by the contribution of the partners; Regarding its economic structure, its most relevant account is the Interest and Discounts Earned with a participation percentage of 92.93% and 94.60% generated by the resources placed from the credits granted by the cooperative; in Expenses, the Operating Expenses account is evidenced with 67.89% and 69.12% for disbursments made to employees. Subsequently, complying with the second specific objective, the financial indicators established by the Superintendency of Popular and Solidarity Economy (SEPS) for savings and credit cooperatives, segment 2, were applied, which allow evaluating the financial-economic position, it was evidenced that Sufficiency Patrimonial has a variation of 1.30% which can solve its patrimony correctly for future decisions, its Liquidity with a variation of 94.66% to cover its short-term debts and Vulnerability to Equity with a percentage of 7.25 % that is enough to respond to possible credit risks. Finally, for the development of the third specific objective, the financial report was prepared in which the results of the analysis carried out were presented in clear and comprehensive language, as well as conclusions and 5 recommendations with the purpose of publicizing the most important points at personal discretion that they will help for the correct decision-making of the administrators, allowing the cooperative to be kept in a good financial position.